A CASE REPORT OF WOODEN STICK IMPALEMENT AND PALPEBRAL RUPTURE : ORBITAL PENETRATION TRAUMA: Poster Presentation - Case Report - Resident - NOVIAN ADI SAPUTRA; MARDIJAS EFENDI; HENDRIANTI (Majalah Oftalmologi Indonesia, 2023)
Introduction : Orbital penetration trauma is a severe injury caused by the penetration of a foreign object into the orbit of the eye. It is a potentially life threatening condition that can cause significant damage to the surrounding structures, including the eye, the optic nerve, and the brain. Case Illustration : 49 y.o M came with The left eye was impaled by a wooden stick 12 hours before entering the hospital, causing pain, bleeding, and loss of vision.Visual acuity of the left eye was no light perception, extensive palpebral rupture, and left eye movement was limited in all directions. The CT scan of left orbit was orbital floor fracture, hypodense lesion in the left retrobulbar oculi which appeared to obliterate the left optic nerve, and orbital floor fracture.He underwent surgery for the removal of the wood and underwent a wide palpebral reconstruction. . Discussion : The severity of orbital penetration trauma can vary depending on several factors, including the size and shape of the penetrating object. In some cases, the injury may be relatively minor and only result in minor bruising and swelling around the eye. However, more severe cases can cause significant damage to the eye itself, including rupture of the eyeball or damage to the optic nerve. Conclusion : Orbital penetration trauma treatments typically involves immediate medical attention to assess the extent of the injury and determine the best course of action. In some cases, surgery may be required to repair the damage and prevent further complications.